MODEL PENENTUAN LOKASI SPBU (STASIUN PENGISIAN BAHAN BAKAR UMUM) MENGGUNAKAN METODE PAIWISE COMPARASION DAN INTERPOLASI KRIGING - Aga Ridha Aldila, Muhammad
One of the sectors that has much attention of foreign investors is the field of oil and natural gas. If the enterpreuners of local gas station cannot make good strategies to deal with this, those foreign investors, inevitably, will dominate the supply of oil and natural gas in Indonesia. In determining the location of gas station, it is needed the strategic location which gives the advantages from sale sector. One of methods to model the potency of gas station location is by using Pairwise Comparison. By considering some landuse parameters to Pairwise Comparison matrix, so it will get the quality value of each parameter which can represent economical value of gas station in a location. Having got quality value of each landuse characteristic then spatial analyst is conduct to produce result quality value of road data originated from Landuse quality value. Interpolation from sale sector is conducted for verification, so we can get a new location which can be representative the potential gas station. The making of model be done in three and tested in Bandung, by making use data of West Java map, with landuse attribute in shapefile format on scale 1 : 25.000 then verification is conducted with data of sale capacity on the average per day from existing location gas station which are located in Bandung to look the level of accuration of the model. The high level accuration of the model is 58%.